THE APPLICATION OF TEACHING OF PARTICIPATION IN THE ROBBING CRIMINAL ACT - Basri Basri; Johny Krisnan (Surakarta Law and Society Journal, 2019)
This study aims to analyze and explain 1) Who are the parties that can be used as a suspect and how its position legally; 2) A criminal offence if the supposition to perpetrators. This study is a normative legal and empirical legal research. The results of the study that